PERILAKU WIRAUSAHA MAHASISWA PESERTA PROGRAM KREATIVITAS MAHASISWA KEWIRAUSAHAAN DAN PROGRAM PENGEMBANGAN KEWIRAUSAHAAN MAHASISWA - Azzahra, Rifzashani; Burhanuddin, Burhanuddin (Forum Agribisnis, 2012)
Bogor Agricultural University is a university that has a great mission about entrepreneurial skill of its students to solve the unemployed problems in Indonesia. The aims of this research are to identify the individual characteristics, to analyze entrepreneurial behavior, and to analyze the correlation between the characteristics and the entrepreneurial behavior of Bogor Agricultural University students who are participated in Student Creativity Program of Entrepreneur and Student Entrepreneur Development Program. The tools to get this aims is Spearman and Chi Square Test which used to see the correlation between the characteristics and the entrepreneurial behavior. Total respondents are 25 which all of the Bogor Agricultural University students who are participated in Student Creativity Program of Entrepreneur and Student Entrepreneur Development Program are taken. The results showed that entrepreneurship knowledge (96 percent very high), the attitude of entrepreneurs (64 percent higher) and entrepreneurial action (84 percent very high) classified as a superior student entrepreneurship. Entrepreneurial behavior is influenced by the students father job (p 0.039 to action), mothers work (p 0.071 to action), tribe (p 0.001 to action), participation in the seminar or training entrepreneurship (p 0.010), and taking courses entrepreneurship (p 0.195). These results provide some recommendations for developing agri-entrepreneurship human resources in Indonesia.